Identification of DNA homologies among H incompatibility group plasmids by restriction enzyme digestion and Southern transfer hybridization. - Whiteley, M (1983)
Plasmids belonging to the three HI plasmid incompatibility subgroups were characterized by the use of restriction enzymes and Southern transfer hybridization. A diversity of restriction enzyme patterns was noted among the HI subgroups, and a small amount of DNA homology was observed by probing these digests with a nick-translated HI1 plasmid. Within a single subgroup (HI1 and HI2), similar restriction enzyme patterns were noted. Plasmids of all three HI subgroups and the HII group had a guanine plus cytosine content of 49 to 50 mol%. The IncHII plasmid pHH1508a also showed some homology with the HI1 probe. The DNA homology observed is probably responsible for common phenotypic properties encoded by these plasmids.